NLRP3 inflammasome upregulates PD-L1 expression and contributes to immune suppression in lymphoma. (28th January 2021) - Lu, Fei; Zhao, Yanan; Pang, Yihua; Ji, Min; Sun, Yanping; Wang, Hongchun; Zou, Jie; Wang, Yan; Li, Guosheng; Sun, Tao; Li, Jingxin; Ma, Daoxin; et al.
Abstract: The NLRP3 inflammasome plays a pro-tumorigenic role in various malignancies. However, its potential role in lymphomagenesis remains unclear. In this study, we identified an immunosuppressive state in patients with diffuse large B cell lymphoma (DLBCL), which was characterized by markedly elevated interleukin (IL)-18 levels in lymphoma tissues and positive correlation with programmed death ligand 1 (PD-L1) expression. Furthermore, NLRP3 inflammasome activation in DLBCL cell lines upregulated PD-L1 and reduced the proportion of cytotoxic T cells. NLRP3 inflammasome blockade in vivo suppressed lymphoma growth and ameliorated anti-tumor immunity by downregulating PD-L1 in the tumor microenvironment and decreasing the proportion of PD-1/TIM-3-expressing T cells, myeloid-derived suppressor cells, tumor-associated macrophages, and regulatory T cells. Further in vivo studies revealed IL-18 as the main effector cytokine involved in the negative regulation of anti-lymphoma immunity. Interestingly, NLRP3 blockers combined with anti-PD-L1 treatment exerted antagonistic effects during lymphoma therapy. Altogether, our findings indicate that NLRP3 inflammasome promotes immunosuppression by modulating PD-L1 and immune cells. Accordingly, this study highlights the prognostic and therapeutic values of the NLRP3 inflammasome in lymphoma. Highlights: NLRP3 inflammasome blockade attenuates lymphoma progression. NLRP3 inflammasome blockade downregulates PD-L1 expression in the TME. NLRP3 inflammasome blockade in vivo reduces the number of immunosuppressive cells. NLRP3 blocker combined with anti-PD-L1 treatment exerts antagonistic effects.